Samba que educa: o potencial do Samba de Roda do Recôncavo Baiano para a educação das relações étnico-raciais - Elzelina Dóris dos Santos (2020)
The aim of this research is to understand the possibilities and educational practices that underlie the Samba de Roda from Recôncavo Baiano, trying to distinguish the formative elements that gives its identity. The research is supported by the Samba de Roda dancers` (sambadeiras) histories of life which are the reference of Samba de Roda from Recôncavo Baiano. Our assumption is that samba has educational possibilities of the racial ethnic relationships for containing elements of African-Brazilian culture and learning processes in which the rhythm, the corporeal, the musicality and the harmony are on the base of the educational relationship. From the path of Samba de Roda from Recôncavo Baiano described by the sambadeiras dialoguing with other samba lyrics, we analyze the educational possibilities in its constitution, history and cultural practices, expecting that this research can contribute to the African-Brazilian culture dialogue in the basic education curriculum. The bibliographic and documentary researches and the interviews with the sambadeiras constituted the methodological path. Nilma Lino Gomes (2015), Nei Lopes (2003), and Kabengele Munanga (2005) are some of the theoretical references that help the dialogue of the researcher with the research subject women through reflection and conceptual discussions about culture, samba history, identity, racial ethnic relationships education